Achene Micromorphology of the Genus Cyanus Mill. (Compositae) in Turkey and its Taxonomic Importance - Şi̇ri̇n, Emrah; Ertuğrul, Kuddi̇si̇; Uysal, Tuna (Phytotaxa, 2017)
Micro- and macromorphological achene features of 20 knapweeds taxa from Turkey were searched using light and scanning electron microscopy. The achene surface was examined in detail for each taxon and a dendogram was established by numerical analyses derived from the observed micromorphological features. Cyanus pinardii was distinguished by epappose while Cyanus depressus was distinguished by longer pappus than achene. The results indicated that the examined taxa had very high variations in their achene surface. According to the results, pericarp texture and color, hilum position and pappus hairs could be used for taxonomical diagnosis of the Cyanus taxa. The hairiness of the surface and elaiosome in the basal of pericarp were characteristic in all Cyanus taxa.